CHALLENGES OF LEARNING ENGLISH AS A SECOND LANGUAGE (ESL) (World Bulletin of Social Sciences, 2025)
This article explores the multifaceted challenges faced by learners of English as a Second Language (ESL). It discusses linguistic, cultural, psychological, and educational barriers that hinder effective acquisition of English, supported by literature analysis and empirical observations. The study also suggests pedagogical methods to address these challenges and improve ESL outcomes.